ChemInform Abstract: A General Strategy for Synthesis of Heterocyclic Hemiketal‐Containing α, β‐Unsaturated Ketones from Ynediones. Issue 22 (12th May 2016) - Zhang, Zeguang; Dai, Zhihong; Jiang, Xuefeng
Abstract: Multiple 3(2H)‐furanones as well as 3(2H)‐thienones endowed with a broad range of aryl, hetaryl, and alkyl groups are efficiently prepared.